An In Vitro Biomechanical Investigation of Compression Plating with Cable Cerclage for Repair of Oblique Osteotomies in Foal Femurs - Frankeny, Rebecca L.; Wilson, D. A.; Carson, W. L.; Keegan, K. G. (Veterinary and Comparative Orthopaedics and Traumatology, 1998)
Long oblique diaphyseal osteotomies were created in 14 pairs of femurs from cadaver foals less than six months of age. One bone from each pair was repaired using two dynamic compression plates (DP), and the other was repaired using a dynamic compression plate with cable cerclage (CC). Seven pairs were tested in compression and seven pairs in craniolateral-caudomedial (CrL-CdM) three-point bending.A difference was not found in mean (± SD) breaking strength in compression between the DP (7257.19 ± 2004.08 N) and CC (7761.41 ± 2552.91 N) techniques. Nor was there a difference in mean stiffness in compression between the DP (2533.83 ± 1777.38 N/mm) and CC (3177.98 ± 1694.70 N/mm) techniques. There was no difference in mean stiffness in three-point bending between the DP (244.60 ± 60.80 N/mm) and CC (195.50 ± 80.90 N/mm) techniques. The mean bending breaking strength and bending moment for the DP technique (2839.36 ± 199.46 N and 124,932.00 ± 8776.38 N mm) was significantly (P = 0.02) greater than the CC technique (1940.39 ± 732.80 N and 85,377.72 ± 32243.34 N mm).The CC system was inferior to the DP technique in CrL-CdM three-point bending strength and moment, but provided equal bending stiffness and equal compressive strength and stiffness.The use of compression plating with cable cerclage was compared to double plating for repair of long oblique osteotomies in foal femurs. The repairs were tested in compression and 3-point bending. The compression plate with cable cerclage was inferior to double plating in bending strength and moment, but provided equal compressive strength and stiffness.
Keywords: Femur fractures; internal fixation; cable cerclage